Тransnationalization of the hotel business of the EU countries - Ganna Gorina; Olha Nikolaichuk (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2024)
The strong attractiveness of the European tourist region leads to a high intensity of market growth and tourist exchanges, the concentration of tourist demand, the generation of innovations, as well as the intensification of the role of tourist TNCs, international hotel and restaurant chains and operators, which in turn requires additional study and analysis. The subject of the study is the organizational and economic foundations of the expansion of the TOP-10 hotel companies with headquarters in EU countries to foreign markets. The purpose of the article is to carry out a comparative analysis of the activities of the TOP-10 international hotel companies with headquarters in the EU countries and to determine on this basis the market leaders, as well as their fluctuation during the analyzed period. The objectivesof the research are to determine the comparative performance indicators of the TOP-10 international hotel companies with headquarters in the EU countries and to conduct a comparative analysis; implementation of the spatial distribution of EU countries according to the number of hotel rooms, as well as their comparison with the base countries of the TOP-10 international hotel companies of the EU (by the number of rooms); study of rating fluctuation of analyzed hotel companies. Research methods: analysis and synthesis; rating; comparative analysis; cartographic method; graphical method. Results. A comparative analysis of the activities of the TOP-10 international hotel companies with headquarters in the EU countries was carried out, according to the indicators of room and hotel funds, country coverage, length of stay in the leaders of the rating. Spatial distribution of EU countries by hotel room stock in 2022 was carried out, their comparison with the base countries of the TOP-10 international hotel companies of the EU (by number of rooms) was carried out. Conclusions and discussion. The conducted comparative analysis made it possible to reach the following conclusions: 1) the entire set of analyzed international hotel companies that are included in the TOP-10 rating are located in three EU countries: France (2 units), Spain (4 units), Germany (4 units). ), which correlates with the ranking of EU countries based on the bedrooms number; 2) despite the crisis phenomena in 2021-2022, there is a prevailing tendency to increase the room stock of hotel operators (60% of the analyzed companies), which is mainly due to the increase of the hotel stock; 3) the most stable position in the world rating for 2017-2022 among hotel operators of EU countries is occupied by the French company Accor, occupying the 6th-7th position. Spanish operators Meliá Hotels Internationa, Barceló Hotel Group and RIU Hotels&Resorts are noted for their relative stability, the fluctuation of their rank does not exceed 6 points. In general, 6 of the TOP-10 hotel companies worsened their global rating, while 4 companies improved; 4) intensive geographical expansion is characteristic of a limited number of companies with headquarters in EU countries, the leaders among which are Accor - 110 countries, Club Med - 40 countries, Meliá Hotels Internationa - 37 countries and Barceló Hotel Group - 25 countries. The practical significance of the obtained results is revealed in the possibility of applying the received analytical data and conclusions for the development of national hotel companies, their expansion to foreign markets.